Comparative Analysis Of Phraseological Units In Uzbekistan And English - O'ktamova, Mokhigul; Madinabonu, Bahodirova (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes commonly used phraseological units in Uzbek and English, highlighting their similarities and differences in meaning and usage. The main focus is on the challenges that arise in the process of translating phraseological units from one language into another, as well as issues of lexical equivalence. The research findings contribute to a deeper understanding of both languages and reveal important aspects of interlingual phraseology.